Effect of monohydroxylated flavonoids on glycation-induced lens opacity and protein aggregation. (1st November 2016) - Patil, Kapil K.; Meshram, Rohan J.; Gacche, Rajesh N.
Abstract: Glycation-induced cataractogenesis and visual impairment is a major ophthalmic concern of altered sugar homeostasis in humans as well as animals. Searching antiglycating agents from natural sources is widely acknowledged as it can be made bioavailable through diet. The present study was designed to understand the positional suitability of hydroxylation in the flavonoid scaffold for maneuvering it as an anticataract agent. Six naturally occurring monohydroxylated flavonoids rataining hydroxylation at 3, 5, 6, 7, 2′ and 4′ carbon position were evaluated for their effect on glycation induced lens opacity, protein aggregation, carbonyl group formation and nontryptophan fluorescence. The selected flavonoids also evaluated for their aldose reductase inhibition: a key enzyme implicated in cataractogenesis. The results of this study clearly demonstrated the stereo-specificity of hydroxyl substitution and focused the significance of 7-hydroxy substitution as a lead scaffold. Overall, the test flavonoids demonstrated considerable anti-cataract activities in context with studied parameters.